Skin cancer incidence rates in Krasnoyarsk Region - T. G. Ruksha; A. Ye. Dettsel; A. B. Salmina; Ye. I. Taksanova; K. A. Dettsel (Бюллетень сибирской медицины)
Skin cancer is one of the most common malignancies and its increasing rates are found all over the world and in the Russian Federation in particular. The paper presents statistical analysis of the data on skin cancer morbidity and mortality rates in Krasnoyarsk Region summarized for the period since 1999 until 2005. Peculiarities of occurrence of this pathology among male and female persons are evaluated, tendencies of epidemiology of these tumors are analyzed, and comparative analysis of skin cancer morbidity in Krasnoyarsk Region with the Russian Federation as a whole and with foreign countries is carried out.